Survey and analysis of awareness, participation, and satisfaction rate of stroke patients in the Xuzhou region regarding rehabilitation and related factors - Yang Huo; Sijie Liang; Quanqing Wei; Yunyun Zhang; Ting Zhang; Jie Xiang (Scientific Reports)
Abstract Post-Rehabilitation is crucial for the recovery of stroke patients after a stroke. However, current research lacks investigations into stroke patients’ awareness of the need for rehabilitation after a stroke. Additionally, there is a shortage of studies assessing the satisfaction levels of stroke patients who have undergone rehabilitation. Investigating the awareness, participation, and satisfaction of stroke patients in the Xuzhou region regarding rehabilitation, with an analysis of relevant factors. A total of 1654 patients diagnosed with stroke at Xuzhou Medical University Affiliated Hospital between January 2021 and June 2022 were selected. Telephone follow-up interviews were conducted with these patients six months to one year after their discharge to collect information. Among 1654 patients, 219 were lost to follow-up, and 337 died. There were 1098 valid samples. Among these, 406 patients (36.98%) were aware that stroke required rehabilitation, 306 patients (27.87%) participated in rehabilitation, and 146 (47.71%) were relatively satisfied with rehabilitation, and 53 (17.32%) were satisfied. There was a positive correlation between mRS score and awareness rate (r = 0.635, p < 0.001), as well as between mRS score and participation rate (r = 0.589, p < 0.001). Conversely, mRS score exhibited a negative correlation with satisfaction rate (r=-0.503, p < 0.001). The awareness, participation, and satisfaction levels of stroke patients regarding post-stroke rehabilitation remain less than ideal. Patients with higher levels of disability have a greater awareness of and participation in post-stroke rehabilitation. However, their satisfaction rates tend to be lower.